HUBUNGAN DAN PENGARUH FAKTOR - FAKTOR RISIKO DESIGN AND BUILD TERHADAP KESUKSESAN PROYEK PEMBANGUNAN SEKOLAH PERMANEN DI KABUPATEN PIDIE JAYA DAN BIREUEN - Faisal Faisal; Abdullah Abdullah; Mochammad Afifuddin (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
The earthquake on December 7, 2016 measuring 6.4 on the Richter Scale (SR), which hit the districts of Pidie, Pidie Jaya and Bireuen, has caused fatalities, damage to infrastructure and public facilities. In an effort to accelerate post-disaster rehabilitation and reconstruction, based on INPRES No. 5 of 2017, Aceh Provincial Building and Environmental Management Work Unit of the Ministry of Public Works and Public Housing, carried out the rebuilding of permanent schools using RISHA construction technology with a system of design and build contracts in Pidie Jaya District and Bireuen. This study aims to analyze the relationship and influence of design and build risk factors on the success of permanent school construction projects in Pidie Jaya and Bireuen Districts. This study uses qualitative and quantitative methods. Respondents were directed at 13 planning personnel, 25 implementing personnel, 21 construction management personnel and 13 owner staff. The independent variables in this study are the risk factors of design and build which consist of the owner management ability factor, procurement process, planning ability, implementation ability, project manager's ability, and project scope factors, while the dependent variable is the success of the project. The results of the study show that there is a low level of relationship between the factors of the project manager's ability, a sufficient level of relationships from the factors of implementation ability, procurement processes and project scope factors, a high level of relationship between planning ability factors and management owner's ability factors to project success. All design and build risk factors have a significant effect on project success, which is 68.8%. The dominant factor affecting project success is the project scope factor, with a regression coefficient of 0.162. In this case if the project scope factor is handled properly by all parties involved, then the success of the project will increase by 16.2%.